The relationship between fundamental legal concepts and detailed rulings in Islamic law: a study of islamic law On partnership and capital - Sadique, Muhammad Abdurrahman (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
A careful study of Islamic legal manuals with the aim of identifying the principal legal theories would indicate that a fundamental legal concept has often served as the basis for all the rulings on a specific area of law. The approach of a school Islamic law to detailed issues on a subject is shaped by the individual theoretical foundation developed by the school pertaining to the area of law concerned. In capital based partnerships, rulings of each school have been directly influenced by the distinct postulation adopted by the school with regard to the essence of shirkah. The perception of each school regarding the core structure of shirkah has dictated the approach of the school to the admissibility of various types of capital, liability of partners, and a multitude of related rulings. In deriving practical solutions to issues of current relevance, it should be ensured that the rulings reflect a uniform underlying theory, without contradiction at any level. This calls for a careful attempt to discover or remodel theoretical foundations of various topics, which could accommodate all related regulations. In safeguarding the theoretical consistency of the Shari‘ah, this aspect is of central importance.